Pretreatment of Sugarcane Bagasse by Hot Compressed Water In The Presences of Acid and Alkaline Promoters - Weerasai, Khatiya; Laosiripojana, Navadol; Champreda, Verawat (International Journal of Engineering and Technology, 2018)
Continual rise in utilization of the depleting fossil fuel leads to environmental concerns related to greenhouse gas release which makes finding sustainable alternative platform industry for the production of fuels, commodity chemicals, and materials from renewable plant biomass of great interest. Pretreatment of the starting biomass is a pre-requisite in sugar platform biorefinery in order to increase enzymatic digestibility of the recalcitrant lignocellulosic materials. In this work, pretreatment of sugarcane bagasse was studied under hot compressed water condition in the presence of several acid/alkali promoters (1.5% H2SO4, 5% NaOH) or alternatively in weak acid (acetic acid) or base (triethylamine (TEA) as the sole reaction medium under low reaction temperatures (80 to 120 °C) for 30 min with pressurized nitrogen gas at 20 bar with continuous stirring at 100 rpm. It was found that the use of base promoters strong base NaOH are efficient in pretreatment under the low temperature in experimental conditions enhancing biomass pretreatment efficiency with high delignification efficiency and high cellulose recovery.
Keywords: Acid/Alkali promoters; Biorefinery; Enzymatic hydrolysis; Lignocellulose